The relationship between service quality and customers' satisfaction in Islamic Banks in Tanzania - Fauz, Mohd Khamis (2014)
This study was intended to examine the relationship between service quality and customers satisfaction in Tanzania Islamic banks. The study applied six service quality dimensions of CARTER model developed by Othman and Owen, (2001) to achieve the intended objectives. Dar-es-salaam and Zanzibar have been selected as the study areas and three Islamic banks (Amana bank, KCB and PBZ) were selected. The study used convenience sampling to get the questionnaire respondents from selected banks. 384 questionnaires were randomly distributed to customers and a total of 255 questionnaire were able to be collected and used for analysis for this study. With the help of SPSS version 19, descriptive analysis, correlation analysis and regression analysis have been used in this study in order to meet research objectives. The findings indicate significant relationship between service quality and customers’ satisfaction. In addition, service quality found to be significant predictor of customers’ satisfaction. However, empathy, compliance and reliability were found to be the only significant predictors of customers’ satisfaction compared to other dimensions. Banks are recommended to improve quality of their services, and provide knowledge to the community about Islamic banking and its products and services. Strong emphasis should be put on those areas that are directly associated with customers service. Moreover, banks must focus on complying with Islamic principles, improving reliability and empathy as these were found to have high effect on customers’ satisfaction.